Oscar de la Renta selling in Amazon luxury stores - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Oscar de la Renta is a luxury fashion brand. Amazon is a multinational e-commerce company known for selling a wide range of affordable products via its marketplace and for extremely fast shipping. The two companies seemingly have little in common. Yet, in September 2020, Amazon announced plans to partner with luxury brands, including Oscar de la Renta, and launched "Luxury Stores." This store, available only via Amazon's mobile website, provides a virtual storefront for invited customers to purchase authentic luxury brand products. This case provides an opportunity for students to assess the opportunities and risks that Luxury Stores provides to Oscar de la Renta-and other luxury brands that sell their products via Luxury Stores-as well as to Amazon. In addition, this case provides a starting point for understanding the marketing of luxury goods more generally, and whether Amazon Luxury Stores is poised for success.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Amazon Web Services (Firm) -- Case studies; Teleshopping -- Case studies; Luxuries -- Case studies